Kualitas Nastar Berempah Wedang Uwuh Berbahan Dasar Mocaf - Muhammad Basyaruddin; Ila Huda Puspita D; Niken Purwidiani; Lilis Sulandari (Pusat Riset dan Inovasi Nasional, 2023)
Wedang uwuh spiced nastar made from mocaf is a dry cake made from mocaf flour, eggs, powdered sugar, butter, cornstarch, and wedang uwuh spice powder. This experiment aims to determine, 1) the hedonic quality of wedang uwuh spiced nastar made from mocaf; 2) knowing the nutritional value, include color, shape, aroma, taste, texture, and overall level of preference; 3) the selling price of the wedang uwuh spiced nastar made from mocaf. This experiment was carried out 4 times to find out the best formula for the wedang uwuh spiced nastar based on mocaf according to the criteria. Based on the experimental results of the wedang uwuh spiced nastar are 1) the product of the wedang uwuh spiced nastar had the criteria, namely: light brown in color, yellowish top, hemispherical in shape, smells of spices, has a sweet taste, tastes of spices, has a fine crumb texture; 2) the nutritional content of wedang uwuh spiced nastar made from mocaf per 100 grams were carbohydrates 61.18%, protein 9.16%, fat 5.62%, water content 21.05%, calories 314.5 kcal, antioxidants 96 .81 mg, and a shelf life of 28.5 days band on microbial growth method at a certain time using a temperature of 28oC; 3) the selling price of wedang uwuh spiced nastar made from mocaf is was IDR 24,437 / 250 grams.